Effect of CALLA metacognitive strategy instruction on reading comprehension and reading awareness - Oxtapianus Tawarik; Ikhsanudin Ikhsanudin; Majid Wajdi; Sorhaila Latip-Yusoph (Journal of Applied Studies in Language, 2021)
This research aim is to analyze whether metacognitive strategy instruction CALLA affects students’ reading comprehension and reading awareness. This research used a quasi-experimental study in forms of pretest, treatment and post-test. Results showed that the group of experimental students had score significantly higher than the control group students on reading comprehension post-test and also showed significantly higher improvement in metacognitive reading strategy awareness and reading comprehension than control group students. The study recommends CALLA metacognitive strategy instruction to be an effective option for teaching reading comprehension skills at the senior high school level and in the contexts, which share similar characteristics.